A Comparative Study of FDI Attractiveness in 3 Arab Spring Countries: Tunisia, Morocco and Egypt - MTAR, Kais; SFAR, Souad BANNOUR Ep (Asian Journal of Economic Modelling, 2017)
There is a considerable body of literature that seeks to shed more light on the determinants of foreign direct investment (FDI), thus offering a wider suite of variables that determine FDI flows. In order to analyze the attractive factors of FDI, several empirical studies have been carried out using different econometric models. The present article is an attempt to identify the determinants of FDI in the form of a comparative study between Tunisia, Morocco and Egypt through a gravity model. The results of the econometric estimate point to the divergence of the main factors of attractiveness in these three countries between the period 1995 and 2010.